DETERMINATION OF CARBARYL IN GROUND WATER BY USING MAGNETIT AS A CORE-SHELL OF MOLECULARLY IMPRINTED POLYMER - Mulyadi, Dikdik
Carbaryl insecticide, one of the carbamate pesticides, has been extensively used for pest control due to their low persistence and high effectiveness. Because its widespread and intensive use, residues of carbaryl have the potential to contaminate the environment. In addition, this residue is toxic, so that it can endanger human healthiness, and a serious problem in the food and processing industry for agricultural products and cause problems of food safety in many places. Many efforts have been made to solve the above issues, by using molecularly imprinted polymer which selective for separatin and analysis of carbaryl in water. But some drawbacks to MIPs have restricted their widespread application, such as slow mass transfer, irregular shape, incomplete template removal, poor site accessibility, or heterogeneous distribution of binding sites. One of the promising alternatives to overcome thisweakness is imparting magnetism to the MIPs and then using magnetic separation. Magnetic separation technology, in which polymers are prepared using fabricating the MIPs on the surface of a magnetic substrate, has received remarkable attention in recent years for its potential application in separation and extraction. Recently, magnetic molecularly imprinted polymers (MMIPs) have attracted significant attention attributing to the fact that they not only exhibit specific selective binding for the template molecule but also have outstanding magnetism